2021
DOI: 10.1249/mss.0000000000002834
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Reverses Amyloid β-Peptide–Mediated Cognitive Deficits in Alzheimer’s Disease Mice Expressing Mutant Presenilin-2

Abstract: PurposeThe molecular mechanisms by which physical exercise produces beneficial effects on pathologic features and behavioral symptoms of Alzheimer’s disease (AD) are not well understood. Herein, we examined whether regular moderate exercise could improve cognitive function and produce transcriptomic responses in the brain.MethodsFour groups of mice were studied: nontransgenic control, mice expressing the human presenilin-2 wild type, mice expressing the human presenilin-2 with the N141I mutation (Tg-PS2m), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The transcriptomic analysis revealed that in AD mice the cell cycle regulatory gene, Cdc28 protein kinase regulatory subunit 2 (Cks2), was decreased while some cell cycle and apoptotic cell death-related factors, including cyclin D1, proliferating cell nuclear antigen, and cleaved caspase-3, were increased in the hippocampus of Tg-PS2m. The treadmill exercise reversed the altered expressions ( Hwang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The transcriptomic analysis revealed that in AD mice the cell cycle regulatory gene, Cdc28 protein kinase regulatory subunit 2 (Cks2), was decreased while some cell cycle and apoptotic cell death-related factors, including cyclin D1, proliferating cell nuclear antigen, and cleaved caspase-3, were increased in the hippocampus of Tg-PS2m. The treadmill exercise reversed the altered expressions ( Hwang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 97%
“…Exercise can boost memory and dampen brain inflammation ( De Miguel et al, 2021 ). The pathologic features and behavioral symptoms of AD caused by the accumulation of amyloid β-peptide in the hippocampus can be reversed by regular exercise ( Hwang et al, 2022 ). Additionally, exercise could promote the motoneuron survival in ALS animals, protect against 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced neurotoxicity in the model mice of PD ( Gerecke et al, 2010 ), and ameliorate striatal deficits in HD model mice ( Pang et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hwang et al evaluated the effect of regular moderate-intensity exercise on improving cognitive function in a mouse model of AD [ 83 ]. Specifically, four groups of mice were included: a control group; a group expressing human wild type presenilin-2 (PS-2), a protein that when mutated determines the onset of AD; a group expressing mutated human PS-2; and a group expressing mutated human PS-2 but subjected to treadmill exercise 50 min a day, 5 days a week, for a total of 6 weeks.…”
Section: Physical Exercise As a Non-pharmacological Strategy To Preve...mentioning
confidence: 99%
“…Interestingly, the group of transgenic animals subjected to exercise showed a greater aptitude for exploring new objects than the untrained transgenic mice. Furthermore, transcriptomic analysis showed an increased expression of factors associated with apoptotic death in the untrained mouse model of AD, suggesting that regular exercise may reverse cellular abnormalities caused by Aβ deposition [ 83 ].…”
Section: Physical Exercise As a Non-pharmacological Strategy To Preve...mentioning
confidence: 99%